Posted by margiee (: ! on Friday, October 24, 2008 at 11:50am.
2. 2x(x+3)=0
There are 2 terms: 2x and (x+3).
If any term in a product is 0 the whole product is 0. So, what value of x would make 2x=0 and what value of x would make x+3 = 0?
x=-3 ?
Sorry, I meant to say factor not term.
If any "factor" in a product is 0 the whole product is 0.
There are 2 "factors".
i still don't understand , i'm sorry .
2x(x+3)=0
I am assuming that you need to find the values of x that will be true for the above.
When you multiply several items (each of these is called a factor) together the answer (called the product) is 0 if ANY of them are 0.
Example:
multiply (a)(b)(c)
If any of them, a or b or c is 0, then multiplying them always gives 0.
The problem has 2 factors:
2x
(x+3)
If either of these is 0 then 2x(x+3) is 0.
The answers are 0 and -3.
It is always a good idea to substitute back to check.
For x=0
2x(x+3)
=2(0)(0+3)
-0(3)
=0
For x=-3
2(-3)(-3 + 3)
=(-6)(0)
=0
The line
-0(3)
should have been
=0(3)
See below:
For x=0
2x(x+3)
=2(0)(0+3)
=0(3)
=0
Aren't you supposed to solve these equations for x?
For #2, if
2x(x+3)=0, then either x = 0 or x = -3 will satisfy equation. Those are the solutions,
For #4, note that x^2 + 3x - 28 =
(x+7)(x-4). Since this is zero, then x = -7 and x = 4 satisfy the original equation, and are solutions
The two equations that you wrote for #5 are inconsistent. If the first one is correct, then what you need to do is factor 2x^2+9x-5
Try (2x-1)(x+5)
If that equals zero, then either factor is zero, and that tells you what x is.
mkay , thanks (:
so , what about number 3 ?
Factor y^2 + 8y = 0 into
y(y+8) = 0, and get the solutions from the factors. We are trying to teach you how to do these by yourself.